Screening a newly developed common bean germplasm with improved resistance to ashy stem blight in multiple environments - Viteri, Diego M.; Linares-Ramírez, Angela M. (Frontiers in Plant Science, 2022)
Ashy stem blight (ASB) caused by the necrotrophic fungus Macrophomina phaseolina (Tassi) Goidanich is an important disease in common bean (Phaseolus vulgaris L.) in the Americas and worldwide. Low to intermediate levels of ASB resistance exist in cultivated and landraces genotypes of common bean and the tertiary gene pool. However, cultivars with higher levels of resistance are not yet available. Our objectives were to: (1) pyramid higher levels of resistance from multiple parents populations within the primary gene pool, and (2) compare the response of the new developed breeding lines (BL) with known sources of resistance. The BL UPR-Mp-22, UPR-Mp-34, UPR-Mp-42, and UPR-Mp-48, known sources of resistance, and susceptible checks were inoculated twice per plant with the PRI21 M. phaseolina isolate in the greenhouse and field trials conducted at Isabela and Lajas, Puerto Rico. None of the genotypes tested were resistant (mean scores 1-3). However, the new black UPR-Mp-42 and white UPR-Mp-48 BL had an intermediate response (4-6) compared to white common bean genotypes ‘Bella’, NY6020-4, and ‘Verano’; and black bean TARS-MST1 that were susceptible (scores ≥ 7) in all environments. Andean genotypes A 195, PRA154, PRA155, and UPR-Mp-22 were intermediate in the greenhouse. In contrast, UPR-Mp-34 had significantly lower scores than BAT 477 that had a susceptible reaction in the greenhouse in Isabela and in the field in Lajas, and SEA 5 that was susceptible in all environments. These new BL possess an enhanced ASB resistance and may be used to improve common bean cultivars or germplasms of different market classes.